Whole Body Interaction with Public Displays - Walter, Robert; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book develops valuable new approaches to digital out-of-home media and digital signage in urban environments. It offers solutions for communicating interactive features of digital signage to passers-by. Digital out-of-home media and digital signage screens are becoming increasingly interactive thanks to touch input technology and gesture recognition. To optimize their conversion rate, interactive public displays must 1) attract attention, 2) communicate to passers-by that they are interactive, 3) explain the interaction, and 4) provide a motivation for passers-by to interact. This book highlights solutions to problems 2 and 3 above. The focus is on whole-body interaction, where the positions and orientations of users and their individual body parts are captured by specialized sensors (e.g., depth cameras). The book presents revealing findings from a field study on communicating interactivity, a laboratory on analysing visual attention, a field study on mid-air gestures,and a field study on using mid-air gestures to select items on interactive public displays.
Introduction -- methodology -- state of the art -- technology -- a field study on communicating interactivity -- visual attention analysis -- a field study on visualizing gesture hints -- a field study on mid-air item selection -- conclusion.
Keywords: Signal processing; User interfaces (Computer systems).; Human-computer interaction; Signal, Speech and Image Processing; User Interfaces and Human Computer Interaction